Analysis Of The Influence Of Public Ownership, Number Of Independent Board Of Commissioners And Company Size On Corporate Reporting Timeliness Of Banking Industries In Indonesia - Loso Judijanto; Rianti Setyawasih; Jemmy Christian Rakinaung; Alfiana; Sukriyadi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to examine how the quantity of independent boards of commissioners, public ownership, firm size, and listing age affect the promptness of corporate online reporting. Quantitative techniques are used in this study. Banking companies listed on the IDX that meet the established criteria comprise the sample, whereas banking companies registered on the IDX make up the population in this study. Purposive sampling was the method of sampling that was applied. Data for this study were gathered through a variety of techniques, including observation, literature review, and documentation study. This study's data analysis approach makes use of quantitative analysis methods like logical regression analysis and descriptive statistical analysis. It is clear from the analysis and discussion that public ownership has little bearing on how quickly corporations report on the internet. The promptness of corporate online reporting is influenced by the size of the company. There is no relationship between listing age and the promptness of corporate online reporting. The promptness of corporate online reporting is unaffected by the number of independent commissioners.